2009
DOI: 10.1177/0960327109105163
|View full text |Cite
|
Sign up to set email alerts
|

Genotoxic effects of nanosized and fine TiO2

Abstract: The in-vitro genotoxicity of nanosized TiO2 rutile and anatase was assessed in comparison with fine TiO2 rutile in human bronchial epithelial BEAS 2B cells using the single-cell gel electrophoresis (comet) assay and the cytokinesis-block micronucleus test. BEAS 2B cells were exposed to eight doses (1—100 μg/cm2) of titanium(IV) oxide nanosized rutile (>95%, <5% amorphous SiO2 coating; 10 × 40 nm), nanosized anata… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
109
3

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 190 publications
(124 citation statements)
references
References 43 publications
10
109
3
Order By: Relevance
“…In the present study, we focused on the effects of one type of NP, nano-TiO 2 , with respect to its different physico-chemical properties, including particle surface modification. The physico-chemical characteristics of the TiO 2 test samples (shown in Table 1) were consistent with findings of others (Falck et al, 2009;Limbach et al, 2005). Particles with smaller sizes possess larger surface areas, have a stronger tendency to agglomerate in medium, and interact more with biomolecules such as proteins and DNA in biological environment.…”
Section: Most Of the Toxicological Results On Nps Have Been Generatedsupporting
confidence: 86%
See 3 more Smart Citations
“…In the present study, we focused on the effects of one type of NP, nano-TiO 2 , with respect to its different physico-chemical properties, including particle surface modification. The physico-chemical characteristics of the TiO 2 test samples (shown in Table 1) were consistent with findings of others (Falck et al, 2009;Limbach et al, 2005). Particles with smaller sizes possess larger surface areas, have a stronger tendency to agglomerate in medium, and interact more with biomolecules such as proteins and DNA in biological environment.…”
Section: Most Of the Toxicological Results On Nps Have Been Generatedsupporting
confidence: 86%
“…Similarly, an in vivo study has shown the induction of DNA breakage in mice cells after exposure to P25-TiO 2 in drinking water (Trouiller et al, 2009). In human bronchial epithelial cells exposed to TiO 2 particles, the oxidative DNA damage was shown to be higher in nano-sized anatase compared to its larger counterparts (Gurr et al, 2005), and nano-sized anatase was more toxic than nano-sized rutile (Falck et al, 2009). Our genotoxicity findings agree with earlier studies in the induction of DNA damage in cells after exposure to nano-TiO 2 , and a stronger induction was observed in nano-sized anatase compared to rutile.…”
Section: Most Of the Toxicological Results On Nps Have Been Generatedmentioning
confidence: 95%
See 2 more Smart Citations
“…Anatase TNPs cause dose-related oxidative DNA damage and micronucleus (MN) formation in A431 and BEAS 2B cells [60,96], as well as sister chromatid exchange at a higher dosage [97]. IMR-90 cells were more sensitive to TNP, showing genotoxicity (ROS-induced DNA adduct formation) [98].…”
Section: Toxicity Of Tnps To Mammalian Cellsmentioning
confidence: 99%